Staffing Needs and Associated Costs in Times of Disaster: An Integrative Review. - Langan, Joanne C.; Krieger, Mary M. (Nursing Economic$)
Strategies to complement nursing staff during response to disasters or public health emergencies are identified in this integrative review. Academic and community volunteers and government-vetted providers augment staff by expanding the labor pool and contribute to the effort at substantial savings.